Examination of Cold-Plaque Screening Technique as a Means to Isolate Low Abundance Genes from Oil Palm (Elaeis Guineensis) Flowers - Lim, Chin Ching (1999)
Genes that are present at low abundance in cells are difficult to clone by using standard molecular biology techniques such as conventional differential screening. In plants, many of these low abundance genes encode transcription factors or proteins involved in signal tranduction. Therefore in this study, a cold-plaque screening technique was used as a means to enrich for low abundance genes from an oil palm male flower cDNA library. When a total of 441 non-hybridising plaques ('cold' plaques) were isolated, 123 clones (opcp population) were found to contain inserts with a minimal size of 500 basepairs and were independent clones. Initial screening of these clones by reverse northern analysis with the same probes used during differential screening and an additional probe from female flower of 6 em showed that these 0PCP clones could be categorised into five subpopulations based on their tissue-specificity and expression levels. 61.8% of the 123 clones were expressed at high abundance with all the three probes (Subpopulation A)whilst 4.1% of the clones were lowly-expressed in both male and female flower tissues (Subpopulation B). 7.3% of the clones were expressed at medium abundance but were male-predominant (Subpopulation C) while 11.4% of the clones were expressed at low abundance and were male-predominant (Subpopulation D) and 15.4% of the clones did not show any detectable expression with any of the probes used (Subpopulation E). Partial sequencing of all clones from subpopulation B, C, D and E as well as eight clones from subpopulation A showed that opcp72 (subpopulation D) is a putative UIP2 (Unusual Floral Organ (UFO) binding protein) homolog, opcpl44 (subpopulation A) encodes elongation factor-la, opcp327 (subpopulation E) encodes a putative RLK 5 (Receptor-like Protein Kinase) homolog and opcp441 (subpopulation A) is a putative fructose 1, 6-bisphosphate aldolase gene. Expression studies on ten opcp clones with two representative clones from each subpopulation showed similar expression profiles where hybridisation signals were detected at the early flower development with higher signals in the meristem tissues but no detectable hybridisation signals in 3.5 em and 6 em male flower, one of the stages used to make the male flower cDNA library. Southern hybridisation of genomic DNA for clone opcp72, opcpl44 and opcp327 showed that these genes are low copy genes.In conclusion the use of cold-plaque screening techniques can result in the isolation of a variety of clones whose expression ranges from low abundance (undetectable in the Northern blots), to those that are lowly expressed during the stages of floral development used to construct the oil palm male-flower cDNA library.